A new regional geography of Europe? The labour market impact of the EU enlargements - Floro Ernesto Caroleo; Francesco Pastore (Institute for the Study of Labor (IZA), 2007)
This paper provides a critical overview and a detailed research agenda for scholars interested in regional studies with a special focus on old and new European Union member states. The focus is on the microeconomic foundations of structural change and its spatially asymmetric impact on labour markets. Structural change has been long neglected, but the availability of new data and the specific nature of economic transition in new member states has brought again this issue to the fore, suggesting that it might provide an explanation also of several typical features of regional imbalances in old member states. The literature provides theoretical reasoning and empirical evidence to confirm this
urn:nbn:de:101:1-2008042215
Keywords: 330; EU-Erweiterung; Strukturwandel; Regionale Arbeitslosigkeit; Regionale Disparität; Arbeitsmobilität; EU-Staaten; Übergangswirtschaft; EU-Staaten (Osteuropa)